Characterization of meat quality traits, fatty acids and volatile compounds in Hu and Tan sheep - Li, Jing; Tang, Chaohua; Yang, Youyou; Hu, Ying; Zhao, Qingyu; Ma, Qing; Yue, Xiangpeng; Li, Fadi; Zhang, Junmin (Frontiers in Nutrition, 2023)
Sheep breed has a major influence on characteristics of meat quality and intramuscular fat (IMF), however, studies into the relationship between sheep breed and meat quality traits rarely consider the large variation in IMF within breed. In this study, groups of 176 Hu and 76 Tan male sheep were established, weaned at 56 days old, with similar weights, and representative samples were selected based on the distribution of IMF in each population, to investigate variations in meat quality, IMF and volatile compound profiles between breeds. Significant differences were observed in drip loss, shear force, cooking loss, and color coordinates between Hu and Tan sheep (p < 0.01). The IMF content and the predominate unsaturated fatty acids, oleic and cis, cis-linoleic acids, were similar. Eighteen out of 53 volatile compounds were identified as important odor contributors. Of these 18 odor-active volatile compounds, no significant concentration differences were detected between breeds. In another 35 volatile compounds, γ-nonalactone was lower in Tan sheep relative to Hu sheep (p < 0.05). In summary, Tan sheep exhibited lower drip loss, higher shear force values, and redder color, had less saturated fatty acids, and contained less γ-nonalactone against Hu sheep. These findings improve understanding of aroma differences between Hu and Tan sheep meat.